Living theatre : - Wilson, Edwin (McGraw-Hill, 2004)
Living Theater: A History conveys the excitement and variety of theater throughout time and the dynamic way in which our interpretation of theater history is informed by contemporary scholarship. Rather than presenting readers with a mere catalog of historical facts and figures, Wilson and Goldfarb set each period in context through an exploration of the social, political and economic conditions of the day, and create a vivid study of the developments in theater during that time. Changes to the third edition include the addition of new biographies of key players in the dramatic world, expanded existing biographies, and a completely revised chapter on early Asian theater